2013
DOI: 10.1002/chem.201301896
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Copper(I)–N‐Heterocyclic Carbene Complexes; Ligand Tuning Facilitates Isolation of the First Structurally Characterised Copper(I)–NHC Containing a Copper(I)–Alkene Interaction

Abstract: The preparation of a series of imidazolium salts bearing N-allyl substituents, and a range of substituents on the second nitrogen atom with varying electronic and steric properties, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…30 The azolium salts include new picolyl linkers, functionalized in the para position with Cl, Me, OMe and NO 2 . The complexes obtained are related to previously reported analogs, of which no photophysical properties have been described, [31][32][33][34][35] and also form monomeric, dimeric and polymeric structures depending on the picolyl donor strength and/or the crystallization method.…”
supporting
confidence: 55%
“…30 The azolium salts include new picolyl linkers, functionalized in the para position with Cl, Me, OMe and NO 2 . The complexes obtained are related to previously reported analogs, of which no photophysical properties have been described, [31][32][33][34][35] and also form monomeric, dimeric and polymeric structures depending on the picolyl donor strength and/or the crystallization method.…”
supporting
confidence: 55%
“…To further support these findings, we undertook an experimental study to examine the effect of a mixed-ligand system. Cu I -NHC complex 8 (bearing an allyl substituent) [34] was allowed to react with 2-bromoimidazolium salt 7 (bearing a mesityl substituent) (1:1) in the presence of one equivalent of CuBr (Scheme 4). NMR spectroscopy and mass spectrometry revealed that the resulting product was a mixture of the hetero-coupled bis-imidazolium dimer 9 and, surprisingly, the homo-coupled product 5 (~20:1).…”
mentioning
confidence: 99%
“…These ligands also represent an interesting scaffold for the synthesis of dinuclear complexes of linear two‐coordinate d 10 group 11 metal ions. For example, the dinuclear Cu I complex II (Figure ) adopts a helical or twisted structure in the solid state with one short Cu I ‐alkene interaction . Similar dinuclear Ag I complexes have been prepared (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Dinuclear Cu I , Ag I , and Au I complexes bearing cyclophane type bis(N‐heterocyclic carbene) ( I ) and arene‐bridged bidentate NHC ligands ( II – IV ). [7a], , , [14a]…”
Section: Introductionmentioning
confidence: 99%